Boundary layer flow and heat transfer of penta-hybrid nanofluid over a permeable slip stretching/shrinking sheet: numerical analysis with logic mining via S2SATRA - Wahid, Nur Syahirah; Romli, Nurul Atiqah; Zamri, Nur Ezlin; Abu Bakar, Shahirah; Mohd Nasir, Nor Ain Azeany; Mohd Jamaludin, Siti Zulaikha; Mohd Kasihmuddin, Mohd Shareduwan; Mansor, Mohd Asyraf; Md Arifin, Norihan; Pop, Ioan (Springer Science and Business Media, 2025)
This study investigates the boundary layer flow of penta-hybrid nanofluid with suction and velocity slip over a stretching/shrinking sheet. The exploration of penta-hybrid nanofluid, which consist of five different nanoparticles, is motivated by the synergistic effects that enhance heat transfer performance. A mathematical model is formulated in the form of partial differential equations based on the fluid flow configuration, which are then reduced to ordinary differential equations and solved numerically using the finite difference scheme in MATLAB. Dual solutions are obtained, and the impacts of various parameters are analyzed. This study demonstrates that penta-hybrid nanofluid with a high concentration of titanium dioxide significantly enhances the heat transfer rate compared to those with lower concentrations, particularly when operating under conditions of lower suction and velocity slip at the boundary, with the sheet in a stretching condition. Additionally, the increase in suction and velocity slip allows the sheet to shrink more extensively, which helps delay boundary layer separation and prevents the turbulent flow. Furthermore, Supervised 2 Satisfiability Reverse Analysis (S2SATRA) is employed to understand parameter interactions and optimize heat transfer performance. The analysis identifies the best-induced logic for accurately predicting the heat transfer rate, which is expressed as: Rex-1/2Nux=( λ∨ϕ5) ∧ (ϕ2∨ϕ1) ∧ (ϕ3∨¬ϕ4) and Rex-1/2Nux = (S∨ϕ4) ∧ (λ∨¬ϕ3) ∧ (A∨ϕ5).